Mapping the Potential of Jawa Tondano Village as a Religious Tourism Village in Minahasa Regency North Sulawesi Province - Plangiten, Novva N.; Ruru, Joorie M.; Pangemanan, Sofia E. (Journal La Bisecoman, 2024)
Minahasa Regency, North Sulawesi Province has many potential resources that continue to be developed to support the tourism sector. However, the government has not yet made local wisdom based on religion a potential to be developed into a tourist destination. The community living in the Jawa Tondano Village has historical value in fighting for the independence of the Unitary State of the Republic of Indonesia and in the spread of Islam in Minahasa Regency. Social interactions that occur with the Minahasa tribe do not fade the value of Javanese ethnic wisdom and the religious nature of the descendants of Kiay Mojo. Kampung Jawa Tondano is a community in Minahasa Regency that has the potential to be developed as cultural-religious tourism based on local wisdom. This study was conducted to analyze the potential of Kampung Jawa Tondano Village physically and non-physically to be developed as a Religious Tourism Village in Minahasa Regency. This study will be conducted using a qualitative design with a case study approach. Data were collected directly through interviews with village government leaders and community leaders and conducted observations to identify all the potential in the Jawa Tondano Village. Secondary data collection was also conducted by utilizing the village profile and searching for references to various electronic publications that are in accordance with the research object. The analysis technique was carried out by means of data reduction, data display and conclusion drawing and verification.